Influencia de la lignina y otros materiales de desecho en el crecimiento de las plantas - Dunn, Stuart (Lilloa, 2022)
Plants are grown in water and sand, with finely ground lignin and other colloidal substances added to modify the texture. None of them had any effect on crops in water or gravel, but they did promote growth in crops in sand. Plants were grown in soil, adding lignin and other organic compounds, both for single crop (non-residual) crops and for successive crops, to observe the residual effects of these substances on consecutive crops in the same soil. In each group, a few isolated crops were shown to have benefited from the treatments, when compared to crops grown in untreated soil. But the mean differences turned out to be unimportant. From there it is concluded that the advantages resulting from these treatments cannot be verified or evidenced in greenhouse crops. These would be due to the increased capacity to retain the nutritive elements against the effects of washing, etc. The aforementioned treatments are far more effective in crops grown in the open field, and under these conditions their possible benefits should be considered. The preliminary test of the speed with which the decomposition process of a fertilizer is carried out, on the other hand, is preferable to carry out in greenhouse crops. The addition of lignin to the soil did not increase the starch content in potatoes, having used plants of the Katandin variety, which is usually characterized by its low percentage of starch. The addition of finely shredded bark seemed to have some value in terms of reducing the toxic effects exerted by high percentages of nutritive salts in the soil, its beneficial effects being otherwise doubtful.